2011
DOI: 10.1111/j.1399-3046.2011.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP3A5 polymorphism on tacrolimus maintenance doses and serum levels after renal transplantation: Age dependency and pharmacological interaction with steroids

Abstract: TAC, MMF and MP are used in pediatric kidney tx. The cytochrome P450 (CYP)3A5 enzyme appears to play a role in TAC metabolism. The aims of this study were to investigate CYP3A5 polymorphism's effect on TAC dosing and the age dependency of TAC dosing by testing blood concentrations, and the interaction between steroids and TAC during the first year after tx. Genomic DNA was extracted and amplified with specific primers. CYP3A5 alleles were confirmed by direct sequencing of PCR products on an automated AB13100 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
32
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 37 publications
(47 reference statements)
10
32
2
Order By: Relevance
“…Our data also confirm literature reports on clinical factors associated with slow tacrolimus metabolizers: male sex [40], age [41,42], HCV positivity [43], and higher BMI [44].…”
Section: Discussionsupporting
confidence: 91%
“…Our data also confirm literature reports on clinical factors associated with slow tacrolimus metabolizers: male sex [40], age [41,42], HCV positivity [43], and higher BMI [44].…”
Section: Discussionsupporting
confidence: 91%
“…Additional factors such as age of the recipient, baseline histological score of the graft and treatment with the CYP3A4 inhibitor, fluconazole, were also found to have an influence. n CYP3A5 polymorphism Whereas CYP3A5 genetic polymorphism has been clearly demonstrated to influence tacrolimus disposition during renal and heart transplantation [6,7,[19][20][21], less information is available regarding pediatric liver transplantation [5,8,22]. Two studies found that donor CYP3A5 genotype influenced tacrolimus dose requirements [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…CYP3A5 diplotypes, i.e., CYP3A5*1/*1 , CYP3A5*1/*3 and CYP3A5*3/*3 determine the phenotype of TAC metabolism as extensive, intermediate and poor metabolizers . Individuals who express the CYP3A5*3/*3 allele, therefore, require lower TAC doses than CYP3A5*1/*1 and CYP3A5*1/*3 alleles to keep the desired TR . A previous study by the current authors demonstrated that the average dose of TAC for the induction phase in those who have CYP3A5*3/*3 , CYP3A5*1/*3 and CYP3A5*1/*1 genotypes were 0.077, 0.097 and 0.142 mg/kg/day .…”
Section: Introductionmentioning
confidence: 63%